Development of Nearpod Based Interactive Science Learning Media to Improve Students Learning Activities and Critical Thinking Ability of Junior High School - Nisa, Ila Kamilatun; Wahyuni, Sri; Budiarso, Aris Singgih (UIN Fatmawati Sukarno Bengkulu, 2023)
In the 21st century, in the 4.0 revolution era, the Ministry of Education and Culture has developed a learning paradigm that states that students are expected to be able to develop abilities, one of which is the ability to think critically. However, in addition to these demands on learning, it is also emphasized to be able to make students carry out learning activities well. One way to increase students' learning activities and critical thinking skills is to develop Nearpod-based interactive science learning media. The purpose of this study was to describe the validity, practicality, and effectiveness of Nearpod-based interactive science learning media to improve the learning activities and critical thinking skills of junior high school students. This type of research is development research using the ADDIE model. The research subjects were 7th B grade students of MTsN 10 Jember. The research results are as follows: The validation results of the three validators were 92.13%, with very valid criteria. The practicality results on the learning implementation sheet show a proportion value of 93.23% with very good criteria. The results of the effectiveness of the media to increase learning activities are effective because there is an increase in the percentage at each meeting and an average of 84.47%, which is included in the very active criteria. The effectiveness of the media to improve critical thinking skills is included in the effective criteria because more than 75% of students have medium or high improvement criteria. Furthermore, the effectiveness of the media based on student responses obtained an average of 84.06% with very good criteria. It can be interpreted that the media developed are valid, practical, and effective for increasing learning activities and students' critical thinking skills.